Gut microbiota and short-chain fatty acids (SCFAs) profiles of normal and overweight school children in Selangor after probiotics administration - Joseph, Narcisse; Vasodavan, Kalidasan; Saipudin, Nurul Ain; Mohd Yusof, Barakatun Nisak; Kumar, Suresh; Amin Nordin, Syafinaz (Elsevier BV, 2019)
Obesity has been on the rise in Malaysia in recent years. The intestinal microbiota potentially influences this condition via its effects on whole-body metabolism and weight management. This study aimed to investigate the effects of probiotic drink ingestion on the intestinal microbiota in 42 school children. The subjects were classified as normal weight and overweight and were further divided into intervention and control groups. Faecal samples were obtained from the children, followed by qPCR analysis of the gut microbiota and high-performance liquid chromatography analysis of short-chain fatty acids (SCFAs). Results suggest that consumption of probiotic drinks is associated with significant alterations in the gut microbiota composition of Lactobacillus spp. and Bifidobacterium spp. (p = 0.002). The total SCFA and propionic acid contents increased significantly from baseline in normal weight children. Significant differences were observed for total SCFAs (p = 0.005) and propionic acid among overweight children (p = 0.001). Consumption of Lactobacillus casei Shirota (LcS)-fermented probiotic drinks potentially altered the gut microbiota composition of Lactobacillus spp. and Bifidobacterium spp. in children, concordant with changes in SCFAs; however, further investigation of this phenomenon is warranted.